A Lemma from Nowhere - Imogen Dickie (Crítica)
This paper uses cases involving empty singular terms (on the one hand, cases of what I call “accidental aboutness-failure”; on the other, cases involving proper names occurring in fictions) to argue for a claim about the goal of ordinary belief-forming activity, and shows how this claim generates new foundations for the theory of reference.